THE EFFECT OF CELEBRITY ENDORSEMENT AND THE REPUTATION OF THE @OOTD FESS FORUM ON CONSUMER BUYING INTEREST IN FASHION PRODUCTS AMONG MILLENNIALS, JAKARTA, 2020. - Virgo Simamora; Novi Theresia Kiak; Maria Prudensia Leda Muga (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
This explanatory study seeks to explain the impact of celebrity endorsement and reputation of the @OOTDFESS Forum as exogenous factors on customers' purchase intentions as endogenous variables. Using the questionnaire, the data was collected from 100 millennials aged 20 to 40 who are residents of DKI Jakarta Province. The hypothesis in this research was tested using the Partial Least Square Modeling (PLS-SEM) methods applied with the software of SmartPLS 3.0. The findings of this study indicate that (1) celebrity endorsers have a positive and significant effect on consumers’ purchasing intention. (2) The reputation of the @OOTDFESS Forum has a positive and significant impact on consumers’ purchasing intention. (3) The celebrity endorsement and the reputation of the @OOTDFESS forum simultaneously have an effect on buying interest. According to this research, celebrity endorsement and the reputation of the @OOTDFESS forum variables cause 66.8% of the changes in consumers' purchasing intentions in the fashion industry.